Effects of 5-aza-2´-deoxycytidine on biological parameters of Achroia grisella F. (Lepidoptera: Pyralidae) - Sak, Olga (Archives of Biological Sciences, 2018)
The non-target effects of 5-aza-2´-deoxycytidine (5-aza-dC), an epigenetically effective agent, were assessed on different life-history traits of two successive generations of Achroia grisella F. (Lepidoptera: Pyralidae) by trophic exposure. The results did not reveal any prominent effect of 5-Aza-dC on emergence times and morphological disorders of offspring of both sexes, and dry weight of F1 females (except for 0.1 mg/ml) and males according to controls. However, 5-Aza-dC caused a considerable decrease in wet weight of F1 females at >0.1 mg/mL and in F1 males only at 0.5 mg/mL. The mean longevity of F1 and F2 females was almost unchanged after exposure to 5-Aza-dC treatment. However, the longevity was considerably shorter, by 16% at a dose of 0.75 mg/mL for F1 males and 28% longer at 1.0 mg/mL for F2 males with respect to the controls. When the two generations were compared with each other in terms of adult longevity, the differences were not significant for the longevity of females, whereas F2 males lived significantly longer than F1 males in all groups except for the control and 0.5 mg/mL groups. 5-Aza-dC also markedly decreased the total number of both offspring but no dose-related alterations were observed. Analysis of the data for the number of viable and damaged eggs laid per F1 females revealed that 5-Aza-dC adversely affected the reproductive potential of A. grisella based on daily and three-day observations. The most striking effect was a decline in fecundity of females by 57% at 1.0 mg/mL. These observations suggest that 5-Aza-dC has a negative effect on developing moth progeny across trophic levels. https://doi.org/10.2298/ABS170622034S Received: June 22, 2017; Revised: August 4, 2017; Accepted: August 9, 2017; Published online: October 4, 2017 How to cite this article: Sak O. Effects of 5-aza-2´-deoxycytidine on biological parameters of Achroia grisella F. (Lepidoptera: Pyralidae). Arch Biol Sci. 2018;70(1):149-58.